160 Feeling the benefit: lupus and the world of welfare. (April 2019) - Booth, Sara; Price, Elizabeth; Walker, Elizabeth
Abstract : Background: This study explores peoples experiences of living and working with SLE whilst simultaneously navigating the contemporary UK welfare system. It is established that SLE is associated with high levels of workplace disability and early retirement from employment, requiring financial support. There is little literature about the experience of claiming benefits whilst living with a fluctuating, invisible medical condition, particularly in young people. Lupus is an exemplar of conditions which affect people in their most productive working years, treatable but not curable, which has profound effects on both educational and employment opportunities. Methods: A cross sectional online qualitative study was carried out of people aged 18 and over who were resident in the UK, with a self-reported diagnosis of lupus, through the LUPUS UK website. Participants responded to questions focusing on their experience of working and/or claiming benefits. Employment data is presented elsewhere. Participants were asked to to quantify (with numerical rating scales) (i) psychological distress associated with income loss resulting from lupus, (ii) the proportion of income lost (iii) any fear experienced of being unable to sustain future employment (iv) levels of anxiety generated by engaging with the benefits system. There was space to describe these experiences and for additional information of the participants choice. Results: A cross sectional online qualitative study was carried out of people aged 18 and over who were resident in the UK, with a self-reported diagnosis of lupus, through the LUPUS UK website. Participants responded to questions focusing on their experience of working and/or claiming benefits. Employment data is presented elsewhere. Participants were asked to to quantify (with numerical rating scales) (i) psychological distress associated with income loss resulting from lupus, (ii) the proportion of income lost (iii) any fear experienced of being unable to sustain future employment (iv) levels of anxiety generated by engaging with the benefits system. There was space to describe these experiences and for additional information of the participants choice. Conclusions: The experience of people with lupus claiming state support has been inadequately defined and explored so that it is variously, and inconsistently, understood, both by those requiring welfare and those administering it. We argue for a concerted focus on these issues in order to articulate more effectively this aspect of the experience of living with a chronic illness. The legislative and policy- driven processes, apparently designed to enable people with illness to live the most active working life possible, are not informed by scientific data, more is needed. The experiences of people with lupus are likely to be relevant to those with other similar illnesses where individuals may require long-term financial support with/out work. Funding Source(s): No external funding required